Genome-wide discovery and development of polymorphic microsatellites from Leishmania panamensis parasites circulating in central Panama. Issue 1 (December 2015) - Restrepo, Carlos; Llanes, Alejandro; Guardia, Carolina; Lleonart, Ricardo
Abstract Background The parasiteLeishmania panamensis is the main cause of leishmaniasis in Panama. The disease is largely uncontrolled, with a rising incidence and no appropriate control measures. While microsatellites are considered some of the best genetic markers to study population genetics and molecular epidemiology in these and other parasites, none has been developed forL. panamensis . Findings Here we have developed and tested a new panel of microsatellites for this species, based on high-throughput genome-wide screening. The new set of microsatellites is composed of seventeen loci, mainly spanning trinucleotide or longer motifs. We have evaluated the sensitivity and specificity of the panel based on a sample of 27 isolates obtained from cutaneous leishmaniasis patients from central Panama and also several reference species from bothL . (Leishmania ) andL . (Viannia ) subgenera. The genetic equilibrium was assessed both intra- and inter-loci, while the reproductive mode was evaluated using several tests. The new SSR panel shows high polymorphism and sensitivity, as well as good specificity. The preliminary data described here forL. panamensis suggest extensive departure from Hardy-Weinberg proportions, significant linkage disequilibrium and strong deficit of heterozygotes. Several recombination tests involving multilocus linkage disequilibrium and a phylogenetic approach allowed rejection of frequent recombination in our dataset. Conclusions The genome-wide strategy described here proved to be useful to identify and test new polymorphic SSR loci inLeishmania . The new panel of polymorphic microsatellites is a valuable contribution to the existing molecular markers for the study of genetic structure and other aspects of this important species.